Post a New Question


posted by .

Plug in (-1) for x. It will look like this:

f(-1) = 4 *(-1) - 3

four times negative 1 equals negative 4, so...

f(-1) = -4 - 3.

negative four minus three is easiest to figure out with a number equals negative seven. So:

f(-1) = -7. And you're done!

here is another one i have no idea how to do. if f(x)=4x-3 how do I find f(-1)

4(-1) - 3

four times negative 1 is negative 4.

So what's




Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question